Formation of coke during the esterification of pyrolysis bio-oil - Wu, L.; Hu, X.; Wang, S.; Mourant, D.; Song, Y.; Li, T.; Li, Chun-Zhu (Royal Society of Chemistry, 2016)
Coke formation during the esterification of bio-oil in alcohols and water over a solid acid catalyst Amberlyst 70 has been investigated. The amounts of coke formed from the acid-treatment of bio-oil in various alcohols are half of that in water. Alcohols stabilize the major components in bio-oil such as sugars, furans, aldehydes, carboxylic acids and phenolics. On the other hand, water promotes the polymerisation of these components. In addition, experimental parameters also affect the coke formation during acid-treatment of bio-oil in alcohols. The elevated reaction temperature, long residence time, and high dosage of catalyst significantly promoted coke formation. The soluble polymeric material and insoluble polymeric material was characterized with FI-IR and UV-florescence spectroscopies. The results show that the coke formed is highly aromatic. The aromatics in bio-oil have a significant contribution to the formation of coke during the esterification of bio-oil.